Colon-Targeted Poly(ADP-ribose) Polymerase Inhibitors Synergize Therapeutic Effects of Mesalazine Against Rat Colitis Induced by 2,4-Dinitrobenzenesulfonic Acid - Changyu Kang; Jaejeong Kim; Yeonhee Jeong; Jin-Wook Yoo; Yunjin Jung (Pharmaceutics)
Background/Objectives: In addition to oncological applications, poly(ADP-ribose) polymerase (PARP) inhibitors have potential as anti-inflammatory agents. Colon-targeted delivery of PARP inhibitors has been evaluated as a pharmaceutical strategy to enhance their safety and therapeutic efficacy against gut inflammation. Methods: Colon-targeted PARP inhibitors 5-aminoisoquinoline (5-AIQ) and 3-aminobenzamide (3-AB) were designed and synthesized by azo coupling with salicylic acid (SA), yielding 5-AIQ azo-linked with SA (AQSA) and 3-AB azo-linked with SA (ABSA). Additional conjugation of AQSA with acidic amino acids yielded glutamic acid-conjugated AQSA (AQSA-Glu) and aspartic acid-conjugated AQSA, which further increased the hydrophilicity of AQSA. Results: The distribution coefficients of PARP inhibitors were lowered by chemical modifications, which correlated well with drug permeability via the Caco-2 cell monolayer. All derivatives were effectively converted to their corresponding PARP inhibitors in the cecal contents. Compared with observations in the oral administration of PARP inhibitors, AQSA-Glu and ABSA resulted in the accumulation of much greater amounts of each PARP inhibitor in the cecum. ABSA accumulated mesalazine (5-ASA) in the cecum to a similar extent as sulfasalazine (SSZ), a colon-targeted 5-ASA prodrug. In the DNBS-induced rat colitis model, AQSA-Glu enhanced the anticolitic potency of 5-AIQ. Furthermore, ABSA was more effective against rat colitis than SSZ or AQSA-Glu, and the anticolitic effects of AQSA-Glu were augmented by combined treatment with a colon-targeted 5-ASA prodrug. In addition, the colon-targeted delivery of PARP inhibitors substantially reduced their systemic absorption. Conclusions: Colon-targeted PARP inhibitors may improve the therapeutic and toxicological properties of inhibitors and synergize the anticolitic effects of 5-ASA.